Board of Directors and Sustainability: Analysis of The Impact of Leadership Characteristics on Environmental Performance in Indonesia - Bintara, Rista; Pernamasari, Rieke; Purwaningsih, Sri (Journal of Financial and Behavioural Accounting, 2024)
This study examines the effect of structural and demographic diversity within boards of directors on corporate environmental performance in Indonesia. Board characteristics analyzed include size, female representation, nationality diversity, tenure, and average age. A quantitative method with panel data combining time-series and cross-sectional data was employed. Secondary data were collected from public companies listed on the Indonesia Stock Exchange (IDX) that published environmental performance reports from 2019 to 2022. A purposive sampling method was used to select firms that met specific criteria. Empirical results show that board characteristics overall significantly influence environmental performance. Specifically, board tenure negatively affects environmental performance, while female representation is positively associated with it. Board size and average age show no significant effect. These findings underscore the importance of board composition in shaping sustainable business practices. Companies are encouraged to align with global trends by embedding environmental considerations into strategic decisions. Boards should recognize the urgency of environmental issues, such as climate change, and integrate sustainability into governance frameworks to enhance long-term corporate performance.